Long-term efficacy analysis of the randomised, phase II TRYPHAENA cardiac safety study: evaluating pertuzumab and trastuzumab plus standard neoadjuvant anthracycline-containing and anthracycline-free chemotherapy regimens in patients with HER2-positive early breast cancer - Schneeweiss, Andreas; Chia, Stephen; Hickish, Tamas; Harvey, Vernon; Eniu, Alexandru; Waldron-Lynch, Maeve; Eng-Wong, Jennifer; Kirk, Sarah; Cortes, Javier (European journal of cancer, 2018)
BACKGROUND: We report long-term efficacy and cardiac safety outcomes in patients with HER2-positive early breast cancer treated with neoadjuvant pertuzumab plus trastuzumab with anthracycline-containing or anthracycline-free chemotherapy. - METHODS: Descriptive efficacy analyses were conducted in patients randomised to group A (cycles 1-6: trastuzumab [8 mg/kg loading dose and 6 mg/kg maintenance] plus pertuzumab [840 mg loading dose and 420 mg maintenance], plus 5-fluorouracil, epirubicin and cyclophosphamide [FEC] [cycles 1-3; 500 mg/m2 5-fluorouracil/100 mg/m2 epirubicin/600 mg/m2 cyclophosphamide] then docetaxel [cycles 4-6; 75 mg/m2, escalated to 100 mg/m2 if well tolerated]), B (cycles 1-3: FEC, cycles 4-6: trastuzumab plus pertuzumab plus docetaxel as mentioned previously) or C (cycles 1-6: trastuzumab plus pertuzumab plus docetaxel [75 mg/m2, without dose escalation], and carboplatin [AUC 6]), five years after randomisation of the last patient. This study is registered with ClinicalTrials.gov, number NCT00976989. - RESULTS: Three-year Kaplan-Meier survival estimates for disease-free survival (DFS) were 87% (95% confidence interval: 79-95), 88% (80-96) and 90% (82-97) in groups A-C, respectively. Progression-free survival (PFS) rates were 89% (81-96), 89% (81-96) and 87% (80-95). DFS hazard ratio for total pathological complete response (tpCR) versus no tpCR was 0.27 (0.11-0.64). During post-treatment follow-up, 2/72 (2.8%), 3/75 (4.0%) and 4/76 (5.4%) patients in groups A-C had any-grade left ventricular systolic dysfunction; eight (11.1%), 12 (16.0%) and nine (11.8%) patients experienced left ventricular ejection fraction declines ≥10% from baseline to <50%. - CONCLUSIONS: Long-term DFS and PFS were similar between groups. Patients who achieved tpCR had improved DFS. No new safety signals were identified.